A systematic review of the current status of carbapenem resistance in Nigeria: Its public health implication for national intervention - Tula, Musa; Enabulele, Onaiwu; Ophori, Endurance; Aziegbemhin, Abumhere; Iyoha, Osaretin; Filgona, Joel (The Nigerian postgraduate medical journal, 2023)
Carbapenem antibiotics are considered one of the most effective and the last-resort antibiotics for the treatment of infections caused by multidrug-resistant Gram-negative bacteria. However, with the advent of carbapenem resistance, it becomes obvious that quality health-care delivery will be hampered if adequate measure is not put in place. This review assessed the prevalence of carbapenem-resistant Gram-negative bacteria (CR-GNB) and also provided an up-to-date position on carbapenem resistance (CR) in Nigeria. Three electronic databases (Google Scholar, PubMed and African Journal online) were searched for relevant literatures, and 38 articles published between January 2013 and June 2022 that met the criteria for inclusion were recruited into the study. The mean prevalence of CR in Nigeria stands at 21.3%, with the southern and northern regions documenting a mean prevalence of 22.0% and 20.9%, respectively. Most of the reviewed articles were from clinical settings (81.6%), with urine samples (38.7%) constituting the most prevalent clinical sample in which CR-GNB were detected. The preponderance of phenotypic methods (55.3%) over molecular method (44.7%), particularly the use of disk diffusion test breakpoint and Modified Hodge test was documented. The most prevalent carbapenem-resistant bacteria were Escherichia coli (50.0%) and Klebsiella pneumoniae (26.3%). The blaNDM and blaVIM were the major reported carbapenemase-encoded genes, particularly among E. coli, K. pneumoniae and Pseudomonas species. This systematic review revealed a mean prevalence of CR-GNB in Nigeria that required urgent attention. Furthermore, the detection of clinically and epidemiologically important carbapenemase coding genes is of public health importance.